(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Odeniyi OA, Olawuyi OJ, Ogunsanya O, Unuofin JO. 2022. Occurrence of common core structure and genotype-specific signatures among the Vibrio of environmentally diverse vended crabs and shrimps from selected Lagos seafood markets, Nigeria. Biodiversitas 23: 3081-3090. This study investigated the occurrence of Vibrio species from the gastrointestinal tract of vended crabs and shrimps using Multiplex polymerase chain reactions (Multiplex PCR) method. Different primer pairs were used to detect the presence of hsp, sodB, SodB-R, ctx, toxR, and Vchol virulent genes in the samples. The phylogenetic relationships among the Vibrio species were determined and the polymorphic information content of selected Vibrio primer products was generated using Powermarker V3.25 Dendo-UPGMA program based on Jaccard’s coefficient. The detection of Vibrio virulence genes confirmed the presence of Vibrio species in the DNA extracts of 19 out of the 60 crustacean samples. Among the Vibrio species, Vibrio parahaemolyticus was the most frequently identified species (47.4%), followed by Vibrio cholerae (36.8%), and Vibrio mimicus (15.8%), while the presence of Vibrio vulnificus was not detected in the crab and shrimp samples. Phylogenetically, the Vp.tdh primer constituted the highest allele number, gene diversity and polymorphic information content of 18.00, 0.9444 and 0.9415, respectively, while the mean of the Vp.tdh and Vp.trh primer sequence combination was polymorphic (0.7153). Among the 19 positive Vibrio strains, different major clusters and subclusters were identified, indicating the relatedness between the identified species. The result of this study indicates that the innocuously vended crab and shrimp samples are indeed reservoirs of pathogenic Vibrio species whose consumption by humans might affect the health of the general populace.